Postnatal surge of adipose-secreted leptin is a robust predictor of fat mass trajectory in mice - Horakova, Olga; Janovska, Petra; Irodenko, Ilaria; Buresova, Jana; van der Stelt, Inge; Stanic, Sara; Haasova, Eliska; Shekhar, Nivasini; Kobets, Tatyana; Keijer, Jaap; Zouhar, Petr; Rossmeisl, Martin; et al. (American journal of physiology. Endocrinology and metabolism, 2024)
The transient postnatal increase in circulating leptin levels, known as leptin surge, may increase later susceptibility to diet-induced obesity in rodents. However, the source of leptin during the surge needs to be better characterized, and the long-term effects of leptin are contradictory. Characterization of the interaction of leptin with the genetic background, sex, and other factors is required. Here, we focused on the impact of circulating leptin levels and several related variables, measured in 2- and 4-wk-old i) obesity-prone C57BL/6 (B6) and ii) obesity-resistant A/J mice. In total, 264 mice of both sexes were used. Posttranscriptionally controlled leptin secretion from subcutaneous white adipose tissue, the largest adipose tissue depot in mice pups, was the primary determinant of plasma leptin levels. When the animals were randomly assigned standard chow or high-fat diet (HFD) between 12 and 24 wk of age, the obesogenic effect of HFD feeding was observed in B6 but not A/J mice. Only leptin levels at 2 wk, i.e., close to the maximum in the postnatal leptin surge, correlated with both body weight (BW) trajectory throughout the life and adiposity of the 24-wk-old mice. Leptin surge explained 13 and 7% of the variance in BW and adiposity of B6 mice, and 9 and 35% of the variance in these parameters in A/J mice, with a minor role of sex. Our results prove the positive correlation between the leptin surge and adiposity in adulthood, reflecting the fundamental biological role of leptin. This role could be compromised in subjects with obesity.NEW & NOTEWORTHY The postnatal surge in circulating leptin levels in mice reflects particularly posttranscriptionally controlled release of this hormone from subcutaneous white adipose tissue. Leptinemia in 2-wk-old pups predicts both body weight and adiposity in adult mice fed a high-fat diet. The extent of these effects depends on genetically determined differences in propensity to obesity between C57BL/6 and A/J mice. The leptin effect on adiposity is compromised in the obesity-prone C57BL/6 mice.
Keywords: obezita; tuková tkáň; mice; adiposity; Diet, High-Fat; Adipose Tissue, White; Female; novorozená zvířata; zvířata; myši; myši inbrední C57BL; Mice; Adiposity; Animals, Newborn; ženské pohlaví; Male; Leptin; leptin; Mice, Inbred C57BL; bílá tuková tkáň; dieta s vysokým obsahem tuků; leptin surge; Obesity; Body Weight; Animals; tělesná hmotnost; mužské pohlaví; obesity; adipozita; Adipose Tissue